Analytic Reasoning Process of High School Students In Solving Quadratic Equation Problems Based on Computational Thinking Skills - Ayu Chinintya Lestari; Yusril Achmad Fatoni; Toto Nusantara; Makbul Musar (Universitas Negeri Surabaya, 2026)
Analytical reasoning and computational thinking are two essential skills in mathematics education, especially in solving complex problems such as quadratic equations. This study aims to describe the analytical reasoning process of high school students in solving quadratic equation problems based on computational thinking skills. This study employs a descriptive qualitative approach, with data collected through tests and interviews with 30 students at a high school in Jember, categorized into three levels of computational thinking skill: high (S1), moderate (S2), and low (S3). One subject from each category was selected as a representative for in-depth analysis based on analytical reasoning indicators adapted from Fisher (2011), namely: problem identification, relationship analysis, strategy formulation, and solution evaluation and justification. The research results indicate that S1 demonstrates coherent and flexible analytic reasoning, characterized by precise problem identification, accurate model formation, adaptive strategy use, and implicit verification of results. S2 showed generally systematic reasoning, especially in translating contextual information into algebraic models and performing procedural operations. However, their analytic reasoning tended to rely on fixed procedures, with limited evaluative judgment or strategic adaptation. In contrast, S3 exhibited fragmented reasoning, difficulties in constructing symbolic models, and minimal solution validation, often caused by challenges in decomposing information and analyzing relational structures. These findings provide insights that can help teachers design more adaptive and effective learning strategies to encourage higher-order thinking skills in students.